THE SOCIAL IDEALS OF MYHAJLO PAVLYK - Возняк, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Revealing the essence of the social ideal of M. Pavlyk, the author highlights orientation thinker priority communalism, as a from of free associations of people and government. Highlights sources of communalism, its principles. It was concluded that the ideal of “hromada’s socialism” M. Pavlyk, as well as other thinker 70-80-years XX-th century was an alternative to the Marxist “state socialism”.